MENGELOLA SUMBER DAYA MANUSIA : UPAYA MENCAPAI KESUKSESAN PASCA-MERGER - Hendrato Setiabudi Nugroho (Universitas Trisakti, 2002)
Merger and acquisition is one of the best external strategy to increase the growth of a company. The superioritay of this strategy is to get the benefit that increases the company performance. Sometimes there is amisundertanding for mergerand acquisition both from the management and the employee that caused the failure of this strategy. Because of that, human resources as one of the valueable asset mustbe well managed whether in pre, process, and after merger, so itcanbe the factor that support the succes of the merger and acquisition. Some problems that might be happened in the process of merger and cquicition and process of merger and acquisition is discussed.